To get vaccinated or not? Social psychological factors associated with vaccination intent for COVID-19. (October 2021) - Baeza-Rivera, María José; Salazar-Fernández, Camila; Araneda-Leal, Leslie; Manríquez-Robles, Diego
Pandemic control not only requires effective COVID-19 vaccines but also that they are accepted by at least 80% of the population. For this reason, understanding the social psychological variables associated with vaccination intent is essential to achieve herd immunity. Drawing on the theory of reasoned action, this study seeks to analyze vaccination intent using the beliefs about vaccine effectiveness, conspiracy theories, and injunctive norms as predictors. A non-probabilistic national online survey was conducted during December 2020. A sample of 1, 033 people in Chile answered a questionnaire with the study variables. Using structural equation models, it was found that vaccination intent was explained in 62.1% by beliefs about vaccine effectiveness and injunctive norms, controlling for age, political orientation, socioeconomic status, educational level, and gender. Specifically, beliefs about vaccine effectiveness are based on people's experience with previous immunization processes, which predict vaccination intent. Regarding injunctive norms, they act by influencing and encouraging vaccination by seeking the approval of significant others. Contrary to expected, conspiracy beliefs were not directly associated with the intention to receive a COVID-19 vaccine but were highly related to lower beliefs about vaccine effectiveness. This study suggests that to enhance the vaccination intent, socio-psychological and structural variables need to be considered.